Intrinsic flame-retardant antioxidant cross-linked polyolefin composite material and preparation method thereof
By introducing side-group grafting polyethylene and halogen-free flame retardant into the polyolefin material, combining low-valent phosphorus elements and benzene ring structure, the problems of poor flammability and durability of polyolefin materials are solved, and the problem of poor flammability and durability of polyolefin materials is achieved Excellent flame retardant and antioxidant properties extend service life and reduce the amount of flame retardant added.
Patent Information
- Application Number
- CN202411295118.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-15
- Publication Date
- 2024-12-17
AI Technical Summary
Polyolefin materials have poor flammability and durability, which hinder their wide application in certain fields, especially in complex environments, the gradual deterioration of material properties, and the migration and precipitation of flame retardants and additives lead to a decline in mechanical and flame retardant properties.
Using intrinsic flame retardant and oxidation-resistant crosslinked polyolefin composite material, materials with good flame retardant and anti-oxidation properties are prepared by combining the side-group grafted polyethylene of the flame retardant unit with halogen-free flame retardant and crosslinking agent. , utilize the synergistic effect of low-valent phosphorus elements and benzene ring structure to improve flame retardant performance.
The flame retardant and oxidation resistance of polyolefin materials are significantly improved, the service life is extended, and the thermal aging performance is significantly improved without adding antioxidants, reducing the amount of flame retardant added.
Smart Images

Figure CN119144080A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of flame-retardant composite materials, and in particular relates to an intrinsic flame-retardant and oxidation-resistant cross-linked polyolefin composite material and a preparation method thereof. Background Art
[0002] Polyolefins are rich in raw materials, cheap, easy to process and have excellent comprehensive performance. Therefore, they are a type of polymer material with the largest output and wide application. Polyethylene and polypropylene products are the most important among polyolefins. The main varieties are polyethylene and some copolymers based on ethylene, such as ethylene-vinyl acetate copolymer, ethylene-acrylic acid or acrylate copolymer, polypropylene and some propylene copolymers, poly-1-butene, poly-4-methyl-1-pentene, cycloolefin polymers, etc., which are widely used in the manufacture of optical instruments, chemical and medical equipment, electronic devices and insulation materials, gas separation membranes and packaging materials, fibers and other fields. However, the poor flammability and durability of polyolefin materials hinder their application in certain fields. Polyolefin materials will face various special service environments during service. Under the coupling of complex environmental factors (high temperature, light, rain, wind and sand, vibration, etc.), the material performance will gradually deteriorate. The flame retardant and other additives added to the material will also migrate and precipitate, which will directly cause the mechanical and flame retardant properties of the material to decrease, resulting in a decrease in the safe service performance and service life of the polyolefin material. Therefore, the design and preparation of intrinsic flame-retardant and antioxidant cross-linked polyolefin composites has broad development prospects.
[0003] Common antioxidants used in polyolefins can be divided into primary antioxidants and secondary antioxidants. Primary antioxidants, known as free radical scavengers, are usually blocked phenols or aromatic amines, which inhibit oxidation by providing a hydrogen atom and competing with the polymer to form peroxide radicals. Secondary antioxidants are usually sulfur, phosphorus and benzene ring-containing compounds, which can decompose the intermediate peroxides in the oxidation process and regenerate the secondary antioxidants. When primary and secondary antioxidants are used at the same time, synergistic effects often occur between the two. Antioxidants are eventually consumed during the use of the material, either due to chemical loss caused by antioxidant activity or physical loss due to their migration to the environment, both of which lead to loss of polymer stability. Antioxidant macromolecularization is an effective way to solve this problem. Small molecule antioxidant monomers are grafted onto polymer chains through appropriate reactions, so that the migration and extractability of the synthesized antioxidants are limited. In addition, olefin-based antioxidants have a high compatibility with the polyolefin matrix, making the antioxidant groups more evenly distributed in the polyolefin material, which can avoid the phase separation problem during the melt blending of the polyolefin material.
[0004] Since phosphorus-containing compounds are a class of excellent flame retardants, substances containing low-valent phosphorus are used as hydroperoxide decomposers. They can reduce hydroperoxides released by polymer materials to alcohols, while they themselves are oxidized to phosphates. For example, phosphites are often used as halogen-free flame retardants and antioxidants. 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO, phosphorus is +1 valence) and diphenylphosphinoyl chloride (DC, phosphorus is +1 valence) are new flame retardant intermediates. Anthracenecarboxylic acid (ACA) rich in benzene ring structure can not only effectively remove free radicals in the substance, play an antioxidant role, but also have a certain flame retardant effect. However, low-valent phosphorus flame retardants mainly improve flame retardant properties through the gas phase flame retardant mechanism, and there are no reports on the flame retardancy and antioxidant research of +1 valence phosphorus-containing flame retardants and polyphenyl ring compounds grafted on the main chain of polyolefins. Therefore, it is of great significance to apply DOPO and DC containing +1 valent phosphorus elements and anthracenecarboxylic acid containing multiple benzene ring structures to the flame retardant and antioxidant research of polyolefin composites. Summary of the invention
[0005] In order to solve the technical problem of poor flame retardancy and thermal aging performance of polyolefin materials, the present invention provides an intrinsic flame retardant and anti-oxidation cross-linked polyolefin composite material and a preparation method thereof. The method of the present invention can not only give the polyolefin composite material good flame retardancy and anti-oxidation properties, but also solve the problem of long-term durability of the flame retardant polyolefin composite material.
[0006] The intrinsic flame-retardant and anti-oxidation cross-linked polyolefin composite material of the present invention comprises the following raw materials in parts by mass:
[0007] 34-82 parts of polyolefin, 10-40 parts of flame retardant unit side-group grafted polyethylene, 16-30 parts of halogen-free flame retardant, and 1-2.5 parts of cross-linking agent.
[0008] Furthermore, the total weight fractions of the polyolefin, the flame retardant unit side-grafted polyethylene and the halogen-free flame retardant is 100 parts.
[0009] The polyolefin is selected from one or more of polyethylene, maleic anhydride grafted polyethylene, polypropylene, maleic anhydride grafted polypropylene, ethylene-vinyl acetate copolymer, maleic anhydride grafted ethylene-vinyl acetate copolymer, polyethylene-octene copolymer, maleic anhydride grafted polyethylene-octene copolymer, ethylene propylene diene rubber, maleic anhydride grafted ethylene propylene diene rubber, styrene-butadiene-styrene block copolymer, hydrogenated styrene-butadiene-styrene block copolymer or maleic anhydride grafted hydrogenated styrene-butadiene-styrene block copolymer, and mixed in any proportion.
[0010] The halogen-free flame retardant is selected from one or more of ammonium polyphosphate, piperazine pyrophosphate, magnesium hydroxide, aluminum hydroxide, hydrotalcite, melamine phosphate, melamine polyphosphate, melamine cyanurate, pentaerythritol, aluminum hypophosphite, aluminum phosphite, expandable graphite, zinc borate, graphene, transition metal disulfide, carbon nanotubes, halloysite, sepiolite, and kaolin, and mixed in any proportion.
[0011] The crosslinking agent is selected from one of diisopropylbenzene peroxide, triallyl cyanurate, triallyl isocyanurate, trimethylolpropane trimethacrylate, trimethylol triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, or a mixture of the above-mentioned two or more ...
[0012] The flame retardant unit side-group grafted polyethylene is formed by hydrolyzing EVA and grafting a flame retardant containing a flame retardant structural unit.
[0013] The flame retardant containing the flame retardant structural unit is a flame retardant containing phosphorus or a benzene ring structure, and the grafting amount is 15-35%.
[0014] The flame retardant containing the flame retardant structural unit is selected from 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), diphenylphosphinyl chloride (DC) or anthracenecarboxylic acid (ACA), etc. The corresponding structural formula is shown below:
[0015]
[0016] The flame retardant unit side group grafted polyethylene is prepared by a method comprising the following steps:
[0017] Step 1: Add EVA to the solvent and stir, and heat to 40°C. After EVA is completely dissolved, add sodium hydroxide ethanol solution and stir at this temperature for 2-5 hours for hydrolysis, then add hydrochloric acid solution for neutralization reaction for 5-10 minutes; after the reaction is completed, pour the reaction solution into distilled water and stir continuously until all the precipitates are precipitated, filter and wash, cut the precipitate into pieces and put it into an 80°C oven for drying for 12 hours to obtain EVA-OH product.
[0018] Step 2: EVA-OH is grafted with a flame retardant containing a flame retardant structural unit, including the following three methods:
[0019] Method 1: Add EVA-OH to the solvent and stir, and heat to 40°C. After EVA-OH is completely dissolved, add diphenylphosphine chloride to the system, stir for 12 hours through nitrogen, wash and dry with anhydrous methanol to obtain flame-retardant unit side group DC grafted polyethylene (EVA-DC).
[0020] Method 2: Add EVA-OH to the solvent and stir, and heat to 40°C. After EVA-OH is completely dissolved, add anthracenecarbonyl chloride ACA-Cl dropwise to the above solution, stir for 12 hours through nitrogen, wash with anhydrous methanol and dry to obtain flame-retardant unit side group ACA grafted polyethylene (EVA-ACA).
[0021] The anthracenecarbonyl chloride is prepared by the following method: using anthracenecarboxylic acid as a raw material, adding thionyl chloride and a solvent into a reaction system, heating to 40-60°C in a nitrogen atmosphere for reaction; cooling to room temperature after the reaction is completed, and recovering the solvent by rotary evaporation to obtain a viscous liquid product, namely anthracenecarbonyl chloride ACA-Cl.
[0022] Method 3: Add EVA-OH and DOPO to the solvent, stir, and heat to 40°C. After EVA-OH and DOPO are completely dissolved, add carbon tetrachloride dropwise to the above solution, stir for 12 hours through nitrogen, wash with anhydrous methanol and dry to obtain flame-retardant unit side group DOPO grafted polyethylene (EVA-DOPO).
[0023] Using the first route, the raw materials are composed of the following by mass:
[0024] 65-85 parts of EVA (VA content 20%-50%), 50-200 parts of ethanol, 0.5-1.5 parts of sodium hydroxide, 50-100 parts of 1 mol / L HCl solution, 200-300 parts of solvent, and 15-35 parts of diphenylphosphine chloride.
[0025] Using the second route, the raw materials are composed of the following by mass:
[0026] 65-85 parts of EVA (VA content 20%-50%), 50-200 parts of ethanol, 0.5-1.5 parts of sodium hydroxide, 50-100 parts of 1 mol / L HCl solution, 200-300 parts of solvent, 15-35 parts of anthracenecarboxylic acid, and 15-35 parts of dichlorothionyl.
[0027] Using the third route, the raw materials are composed of the following by mass:
[0028] 65-85 parts of EVA (VA content 20%-50%), 50-200 parts of ethanol, 0.5-1.5 parts of sodium hydroxide, 50-100 parts of 1 mol / L HCl solution, 200-300 parts of solvent, 15-35 parts of DOPO, and 15-35 parts of carbon tetrachloride.
[0029] The solvent is selected from one or more of ethanol, N,N-dimethylformamide, tetrahydrofuran, dichloromethane, chloroform, and 1,4-dioxane. The mass fraction of the above solvents is the total amount of solvents used in the preparation process.
[0030] The method for preparing the intrinsic flame retardant and oxidation resistant cross-linked polyolefin composite material of the present invention comprises the following steps:
[0031] 10-40 parts of flame retardant unit side-grafted polyethylene and 16-30 parts of halogen-free flame retardant are added to 34-82 parts of polyolefin, and the mixture is kneaded in an internal mixer or an extruder at 120-180° C. until uniform. Then 1-2.5 parts of a crosslinking agent is added, and after uniform mixing, the mixture is pressed into a sheet in a flat vulcanizer, and a crosslinked polyolefin composite material is prepared by thermal vulcanization crosslinking or radiation crosslinking.
[0032] If hot vulcanization cross-linking is adopted, vulcanize at 160-200℃ for 15 minutes in a flat vulcanizer or cable hot vulcanization pipeline.
[0033] If radiation cross-linking is adopted, radiation cross-linking is carried out under irradiation of a high-energy electron beam or a cobalt source at an irradiation dose of 200 KGy to produce a radiation cross-linked polyolefin sheet or plate.
[0034] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0035] 1. The intrinsic flame retardant and oxidation-resistant cross-linked polyolefin provided by the present invention has excellent flame retardant properties. The flame retardant unit side group polyethylene replaces part of the EVA resin by hydrolyzing and grafting different flame retardant structural units onto EVA, and its advantages are mainly reflected in the following three aspects: (1) The flame retardant unit side group grafted polyethylene has good compatibility with polyolefin resin, and good dispersion is conducive to improving the flame retardant properties of the polyolefin composite material, and at the same time greatly improves the mechanical properties of the polyolefin material; (2) EVA grafted with different flame retardant structural units makes the matrix contain a benzene ring structure with carbonization function and a phosphorus element that promotes carbonization, and the matrix resin itself has a certain flame retardant level; (3) The flame retardant unit side group grafted polyethylene can play a synergistic flame retardant role with the added halogen-free flame retardant. The flame retardant unit side group grafted polyethylene can play a gas phase flame retardant role of low-valent phosphorus, and the added halogen-free flame retardant plays a condensed phase flame retardant role. The two flame retardant mechanisms cooperate to improve the flame retardant properties of the intrinsic flame retardant polyolefin composite material and the flame retardant difference, thereby achieving the same flame retardant level while reducing the amount of flame retardant added, thereby improving the comprehensive physical properties of the polyolefin material. Therefore, the intrinsic flame retardant and antioxidant cross-linked polyolefin composite material has excellent flame retardant properties.
[0036] 2. The intrinsic flame retardant and anti-oxidation cross-linked polyolefin composite material provided by the present invention has excellent antioxidant performance and long life. (1) The low-valent (+1 valence) phosphorus element in the flame retardant unit side-grafted polyethylene can play the role of an auxiliary antioxidant. As a hydroperoxide decomposer, it can reduce the hydroperoxide released by the polymer material to alcohol, while it itself is oxidized to phosphate ester; (2) The benzene ring structure in the flame retardant unit side-grafted polyethylene can not only effectively remove free radicals in the material body and play an antioxidant role, but also improve the temperature resistance grade and long-term aging resistance of the polyolefin composite material; (3) The cross-linked polyolefin composite material is subjected to long-term accelerated thermal aging test in a high-temperature oven at 180°C and 165°C, which can prove that the intrinsic flame retardant and anti-oxidation cross-linked polyolefin composite material of the present invention can significantly improve the thermal aging performance, long-term anti-aging performance and service life of the flame retardant polyolefin composite material without adding an external antioxidant. Therefore, the intrinsic flame retardant and anti-oxidation cross-linked polyolefin composite material has good long-term antioxidant performance without adding an antioxidant. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 Phosphorus spectra (a) and hydrogen spectra (b) of DOPO and EVA-DOPO.
[0038] Figure 2 Dynamic thermomechanical properties analysis of EVA and EVA-DOPO.
[0039] Figure 3 HRR and THR curves of EVA and EVA-DOPO.
[0040] Figure 4 : Hydrogen spectra of EVA-OH (a) and EVA-ACA (b).
[0041] Figure 5 Dynamic thermomechanical properties analysis of EVA-OH and EVA-ACA.
[0042] Figure 6 The hydrogen spectrum (a) and phosphorus spectrum (b) of EVA-DC.
[0043] Figure 7 A graph showing the relationship between the retention rate of the elongation at break of the sample in Example 2 and time under certain temperature conditions.
[0044] Figure 8 Photograph of the carbon residue of the sample in Example 2 after the cone calorimeter test.
[0045] Fig. 9 A graph showing the relationship between the retention rate of the elongation at break of the sample in Example 3 and time under certain temperature conditions.
[0046] Fig.10Photograph of the carbon residue of the sample in Example 3 after the cone calorimeter test.
[0047] Fig.11 A graph showing the relationship between the retention rate of the elongation at break of the sample in Example 4 and time under certain temperature conditions.
[0048] Fig.12 Photograph of the carbon residue of the sample in Example 4 after the cone calorimeter test. DETAILED DESCRIPTION
[0049] In order to further illustrate the technical solution of the present invention, the preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0050] Embodiment 1:
[0051] a. Preparation of EVA-OH
[0052] Take a 500ml three-necked flask, first dissolve 25g of EVA (VA content 20%) in tetrahydrofuran solution, then slowly drop 40mL of sodium hydroxide / ethanol solution (0.5mol / L), and apply a reflux condenser, react at 40℃ for 5h under mechanical stirring. After the reaction is completed, add 22.5mL of HCl solution (1mol / L) to neutralize the mixed solution, stir for 10 minutes, and stop the reaction. Pour into 500ml of distilled water, stir continuously until precipitation occurs, filter, wash, cut up the precipitate, and dry the product at 60℃ for 12h to obtain EVA-OH.
[0053] b. Preparation of EVA-DOPO
[0054] Take a 500ml three-necked flask, add 20g EVA-OH, 3g DOPO and 200ml dichloromethane, stir and heat to 40℃, after the reactants are completely dissolved, add 7.94g carbon tetrachloride, and stir for 12h under nitrogen. After the reaction is completed, pour into 500ml distilled water, stir continuously until a precipitate is precipitated, filter, wash, cut up the precipitate, and dry the product at 60℃ for 12h to obtain EVA-DOPO.
[0055] c. Preparation of ACA-Cl
[0056] 4.44 g (0.02 mol) of anthracenecarboxylic acid (ACA) was added into a 250 mL three-necked flask, and 100 mL of chloroform was added to dissolve it. 4 mL of thionyl chloride was slowly added dropwise under nitrogen protection, and the mixture was reacted at 50 °C for 5 h. After the reaction was completed, the solvent and unreacted thionyl chloride were removed by distillation under reduced pressure to obtain anthracenecarboxylic acid chloride (ACA-Cl).
[0057] d. Preparation of EVA-ACA
[0058] Take a 500ml three-necked flask, add 20g EVA-OH and 200ml chloroform, stir and heat to 40℃, after the reactant is completely dissolved, slowly add 5g ACA-Cl, and stir for 12h under nitrogen. After the reaction is completed, pour into 500ml distilled water, stir continuously until the precipitate is precipitated, filter, wash, cut the precipitate into pieces, and dry the product at 60℃ for 12h to obtain EVA-ACA.
[0059] e. Preparation of EVA-DC
[0060] Take a 500ml three-necked flask, add 20g EVA-OH and 200ml tetrahydrofuran, stir and heat to 40℃, after the reactant is completely dissolved, slowly add 6g DC, and stir for 12h under nitrogen. After the reaction is completed, pour into 500ml distilled water, stir continuously until precipitation occurs, filter, wash, cut up the precipitate, and dry the product at 60℃ for 12h to obtain EVA-DC.
[0061] Embodiment 2:
[0062] EVA-DOPO was obtained according to Example 1, and 16 parts of intumescent flame retardant (ammonium polyphosphate APP and carbonizing agent CFA) were added to 44 parts of EVA (VA content 28%) and 40 parts of EVA-DOPO according to the mass ratio, and then mixed in an internal mixer or an extruder at 130° C. until uniform, and then 1.4 parts of triallyl cyanurate (TAIC) and 0.6 parts of diisopropylbenzene peroxide (DCP) were added. After mixing evenly, the mixture was vulcanized in a vulcanizer at 165° C. for 15 minutes to make a plate.
[0063] To further verify the performance of EVA-DOPO, we designed the following Figure 7 , 8 The comparison formula shown is used to compare the comprehensive physical property test results of the two. Table 1 shows the addition amount of each component in the mixing formula and the vertical combustion (UL-94) and limiting oxygen index (LOI) test results; Table 2 shows the mechanical properties and combustion performance (Cone) test results of the samples; Figure 7 It is a curve showing the relationship between the retention rate of the breaking elongation and time when the samples are placed in a 180℃ heat aging oven and a 165℃ heat aging oven for about 14 days.
[0064] Table 1 The amount of each component added in the mixing formula and the vertical combustion (UL-94) and limiting oxygen index (LOI) test results
[0065]
[0066] Table 2 Test results of mechanical properties and combustion performance (Cone) of the samples
[0067]
[0068] Embodiment 3:
[0069] According to Example 1, EVA-ACA is obtained, and 10 parts of melamine cyanurate (MPP) and aluminum hypophosphite (AHP) are added to 40 parts of EPDM and 40 parts of EVA-ACA according to the mass ratio, and then mixed at 180° C. in an internal mixer or an extruder until uniform, and then 1 part of trimethylolpropane trimethacrylate (PETA) is added. After mixing evenly, the mixture is irradiated and cross-linked under high-energy electron beam irradiation at a irradiation dose of 200 KGy to prepare a radiation-cross-linked polyethylene sheet or plate.
[0070] To further verify the performance of EVA-ACA, we designed the following Fig. 9 , 10 The comparative formula shown is used to compare the comprehensive physical property test results of the two. Table 3 shows the addition amount of each component in the mixing formula and the vertical combustion (UL-94) and limiting oxygen index (LOI) test results; Table 4 shows the mechanical properties, combustion performance (Cone) and smoke density (Ds) test results of the samples; Fig. 9 The graph is a relationship between the retention rate of elongation at break and time when each sample is placed in a heat aging oven at 180°C and 165°C for about 14 days.
[0071] Table 3 The amount of each component added in the mixing formula and the vertical combustion (UL-94) and limiting oxygen index (LOI) test results
[0072]
[0073] Table 4 Test results of mechanical properties and combustion performance (Cone) of the samples
[0074]
[0075] Embodiment 4:
[0076] According to Example 1, EVA-DC is obtained, and 13 parts of melamine cyanurate (MPP) and piperazine pyrophosphate (PAPP) are added to 34 parts of SEBS and 40 parts of EVA-DC according to the mass ratio, and then mixed in an internal mixer or an extruder at 160° C. until uniform, and then 1.5 parts of triallyl cyanurate (TAIC) and 0.6 parts of diisopropylbenzene peroxide (DCP) are added. After mixing evenly, the mixture is vulcanized in a vulcanizer at 160° C. for 15 minutes to prepare a plate.
[0077] To further verify the performance of EVA-DC, we designed the following Fig.11 , 12 The comparative formula shown is used to compare the comprehensive physical property test results of the two. Table 5 shows the addition amount of each component in the mixing formula and the vertical combustion (UL-94) and limiting oxygen index (LOI) test results; Table 6 shows the mechanical properties, combustion performance (Cone) and smoke density (Ds) test results of the samples; Fig.11 The graph is a relationship between the retention rate of elongation at break and time when each sample is placed in a heat aging oven at 180°C and 165°C for about 14 days.
[0078] Table 5 The amount of each component added in the mixing formula and the vertical combustion (UL-94) and limiting oxygen index (LOI) test results
[0079]
[0080] Table 6 Test results of mechanical properties and combustion performance (Cone) of the samples
[0081]
[0082] Based on the above experimental results, the following conclusions are drawn:
[0083] (1) The synthesized intrinsic flame retardant and antioxidant polyolefin has excellent flame retardant properties and can be compounded with other polyolefin resins to prepare polyolefin composites.
[0084] (2) The intrinsic flame retardant and antioxidant polyolefin composite material with flame retardant unit side-group grafted polyethylene, after heat aging test at 180°C and 165°C for 14 days, the degree of mechanical property degradation is significantly better than that of the control group. Therefore, the intrinsic flame retardant and antioxidant cross-linked polyolefin composite material and the preparation method thereof provided by the present invention not only give the polyolefin material good flame retardant properties, but also improve the long-term heat aging resistance of the polyolefin composite material, and can be used for cable sheath materials.
[0085] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An intrinsic flame retardant and antioxidant cross-linked polyolefin composite material, characterized in that The raw materials are composed by mass as follows: 34-82 parts of polyolefin, 10-40 parts of flame retardant unit side-group grafted polyethylene, 16-30 parts of halogen-free flame retardant, 1-2.5 parts of cross-linking agent; The flame retardant unit side-group grafted polyethylene is formed by hydrolyzing EVA and grafting a flame retardant containing a flame retardant structural unit.
2. The intrinsic flame retardant and antioxidant cross-linked polyolefin composite material according to claim 1, characterized in that: The total weight fractions of the polyolefin, the flame retardant unit side-grafted polyethylene and the halogen-free flame retardant are 100 parts.
3. The intrinsic flame retardant and antioxidant cross-linked polyolefin composite material according to claim 1, characterized in that: The flame retardant containing the flame retardant structural unit is a flame retardant containing phosphorus or a benzene ring structure, and the grafting amount is 15-35%.
4. The intrinsic flame retardant and oxidation resistant cross-linked polyolefin composite material according to claim 3, characterized in that: The flame retardant containing the flame retardant structural unit is selected from 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, diphenylphosphinyl chloride or anthracenecarboxylic acid.
5. The intrinsic flame retardant and antioxidant cross-linked polyolefin composite material according to claim 4, characterized in that The flame retardant unit side group grafted polyethylene is prepared by a method comprising the following steps: Step 1: Add EVA to the solvent and stir, and heat to 40°C. After EVA is completely dissolved, add sodium hydroxide ethanol solution and stir at this temperature for 2-5 hours for hydrolysis, and then add hydrochloric acid solution for neutralization reaction; after the reaction is completed, pour the reaction solution into distilled water and stir continuously until all precipitates are precipitated, filter, wash and dry to obtain EVA-OH product; Step 2: Add EVA-OH to the solvent and stir, and heat to 40°C. After EVA-OH is completely dissolved, add diphenylphosphine chloride to the system, stir for 12 hours through nitrogen, wash and dry with anhydrous methanol to obtain flame-retardant unit side group DC grafted polyethylene.
6. The intrinsic flame retardant and antioxidant cross-linked polyolefin composite material according to claim 4, characterized in that The flame retardant unit side group grafted polyethylene is prepared by a method comprising the following steps: Step 1: Add EVA to the solvent and stir, and heat to 40°C. After EVA is completely dissolved, add sodium hydroxide ethanol solution and stir at this temperature for 2-5 hours for hydrolysis, and then add hydrochloric acid solution for neutralization reaction; after the reaction is completed, pour the reaction solution into distilled water and stir continuously until all precipitates are precipitated, filter, wash and dry to obtain EVA-OH product; Step 2: With anthracenecarboxylic acid as a raw material, thionyl chloride and a solvent are added to the reaction system, and the temperature is raised to 40-60°C in a nitrogen atmosphere for reaction; after the reaction is completed, the temperature is lowered to room temperature, and the solvent is recovered by rotary evaporation to obtain a viscous liquid product, namely anthracenecarboxylic acid chloride ACA-Cl; EVA-OH is added to the solvent and stirred, and the temperature is raised to 40°C. After EVA-OH is completely dissolved, anthracenecarboxylic acid chloride ACA-Cl is added dropwise to the above solution, and nitrogen is passed through and stirred for 12 hours, and the solution is washed and dried with anhydrous methanol to obtain a flame-retardant unit side group ACA grafted polyethylene.
7. The intrinsic flame retardant and antioxidant cross-linked polyolefin composite material according to claim 4, characterized in that The flame retardant unit side group grafted polyethylene is prepared by a method comprising the following steps: Step 1: Add EVA to the solvent and stir, and heat to 40°C. After EVA is completely dissolved, add sodium hydroxide ethanol solution and stir at this temperature for 2-5 hours for hydrolysis, and then add hydrochloric acid solution for neutralization reaction; after the reaction is completed, pour the reaction solution into distilled water and stir continuously until all the precipitates are precipitated, filter, wash and dry to obtain EVA-OH product. Step 2: Add EVA-OH and DOPO to the solvent, stir, and heat to 40°C. After EVA-OH and DOPO are completely dissolved, add carbon tetrachloride dropwise to the above solution, stir for 12 hours under nitrogen, wash with anhydrous methanol, and dry to obtain flame-retardant unit side group DOPO grafted polyethylene.
8. The method for preparing the intrinsic flame retardant and antioxidant cross-linked polyolefin composite material according to any one of claims 1 to 7, characterized in that The steps include: Flame-retardant unit side-grafted polyethylene and halogen-free flame retardant are added to polyolefin, mixed in an internal mixer or extruder at 120-180° C. until uniform, then a cross-linking agent is added, mixed uniformly, and pressed into a sheet in a flat vulcanizer, and a cross-linked polyolefin composite material is prepared by thermal vulcanization cross-linking or radiation cross-linking.
9. The preparation method according to claim 8, characterized in that: Use hot vulcanization cross-linking and vulcanize at 160-200℃ for 15 minutes in a flat vulcanizer or cable hot vulcanization pipeline.
10. The preparation method according to claim 8, characterized in that: The radiation cross-linking is carried out under the irradiation of high-energy electron beam or cobalt source at an irradiation dose of 200KGy to produce a radiation cross-linked polyolefin sheet or plate.
Citation Information
Patent Citations
Radiation cross-linking waterproof flame retardant polyolefin nano-composite material and preparation method thereof
CN101899183A
Flame-retardant monomer containing DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) groups and preparation method and application of flame-retardant monomer
CN103755742A
Phosphorus-containing flame-retardant rigid polypropylene material and preparation method thereof
CN112175310A
Cited By
Graft-modified anti-aging flame-retardant polypropylene and preparation method thereof
CN120059061A
A graft-modified anti-aging and flame-retardant polypropylene and its preparation method
CN120059061B
